Security Design of Safety Deposit Box Based on Microcontroller AT89S52 - Ivan C. Melalolin (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2013)
Automatic safety deposit box is a type of safe that is designed to work to secure any valuables with safety devices that are reliable. Safe uses a motion sensor as detection of human activity in the area before safe. Magnetic sensors to detect the presence of a safe deposit box at the door is opened or closed with a locking solenoid automatic. Safe is designed differently by having two doors where both doors are in and serve as a safety in the first door cracked. The second door has an electric circuit shock. Access to safe uses two types of passwords can be changed by the owner. Another advantage is that using a GSM modem as a liaison between the safes with the owner. Each execution of the safe will be notified to the owner via text message to mobile phone owners. Number to be replaced as well as desired. Each character passwords and destination number will be displayed on the LCD. Safe also features an alarm and LED indicator.